Neonatal herpes simplex pneumonia. Issue 7 (July 1984) - Lissauer, T J; Shaw, P J; Underhill, G
Abstract : A neonate with herpes simplex pneumonia is described. Herpes simplex infection should be considered in the differential diagnosis of pneumonia in newborn infants, even in the absence of clinically apparent herpes in the mother.